Tarramba leucaena: A success story for smallholder bull fattening in eastern Indonesia - Jacob Nulik; Debora Kana Hau; Michael J. Halliday; H. Max Shelton (Tropical Grasslands-Forrajes Tropicales, 2019)
Keynote paper presented at the International Leucaena Conference, 1‒3 November 2018, Brisbane, Queensland, Australia.